Differences between medical school and PGY1 learning outcomes: An explanation for new graduates not being "work ready"?. (1st September 2020) - Ellis, Pete M.; Wilkinson, Tim J.; Hu, Wendy C-Y.
Abstract: Background: Widespread concerns about new medical graduates' 'work readiness' may reflect, in part, differences in mandatory learning outcomes for medical students and new medical graduates. Purpose: To examine differences between required medical student and PGY1 (first year resident) training program outcomes, and the nature and magnitude of these differences. Method: Comparison, systematic identification and thematic analysis of differences between the graduate outcomes in the Australian Medical Council Standards for the Assessment and Accreditation of Primary Medical Programs and those in the New Zealand Curriculum Framework for Prevocational Training. Results: The relationship between these outcome statements were categorized as: essentially similar; continuity; partial discontinuity; and complete discontinuity of learning trajectory. Areas requiring substantial new learning may reflect medical schools' focus on individual student performance, and on learning and assessments based on single episodes of often uncomplicated illness. This contrasted with a post-graduate focus on integrated health care delivery by teams and management of complex illnesses over the whole patient care journey. Conclusions: Characterizing these marked differences between pre-graduate and postgraduate standards, within a trajectory of learning, explains some of the difficulties in students' preparation for work readiness. These could inform learning interventions to support new graduates' professional development to ensure patient safety. Development and revision of accreditation standards should include formal review against the expectations of the preceding and succeeding phases of learning.